MENINGKATKAN MOTIVASI DAN SIKAP POSITIF MAHASISWA DALAM PERKULIAHAN BIMBINGAN DAN KONSELING KARIR MELALUI PEMBELAJARAN KOOPERATIF DAN VARIASI INTERAKSI - Khairani Khairani (Pedagogi: Jurnal Ilmu Pendidikan, 2015)
Motivation and positive attitude in learning activities is the need to be owned by the student to be successful in achieving the learning objectives. This research aims to increase student motivation and positive attitude in lectures using cooperative learning and interaction varies, because reality shows there are still students who have a negative attitude in lectures. This study classified the action research, which was implemented in three cycles, each cycle consisting of planning, action, evaluation and reflection. The subjects were students of BK Career period of 2012 totaling 37 people. The results showed that 97% of students expressed have increased motivation and a positive attitude in lectures.